Cumulative incidence of SARS‐CoV‐2 infection in the general population of the Valencian Community (Spain) after the surge of the Omicron BA.1 variant. Issue 1 (11th November 2022) - Camacho, Jorge; Giménez, Estela; Albert, Eliseo; Zulaica, Joao; Álvarez‐Rodríguez, Beatriz; Torres, Ignacio; Rusu, Luciana; Burgos, Javier S.; Peiró, Salvador; Vanaclocha, Hermelinda; Limón, Ramón; Alcaraz, María Jesús; et al.
Abstract: Studies investigating the cumulative incidence of and immune status against SARS‐CoV‐2 infection provide valuable information for shaping public health decision‐making. A cross‐sectional study on 935 participants, conducted in the Valencian Community (VC), measuring anti‐SARS‐CoV‐2‐receptor binding domain‐RBD‐total antibodies and anti‐Nucleocapsid (N)‐IgGs via electrochemiluminescence assays. Quantitation of neutralizing antibodies (NtAb) against ancestral and Omicron BA.1 and BA.2 variants and enumeration of SARS‐CoV‐2‐S specific‐IFNγ‐producing CD4 + and CD8 + T cells was performed in 100 and 137 participants, respectively. The weighted cumulative incidence was 51.9% (95% confidence interval [CI]: 48.7–55.1) and was inversely related to age. Anti‐RBD total antibodies were detected in 97% of participants; vaccinated and SARS‐CoV‐2‐experienced (VAC‐ex; n = 442) presented higher levels ( p < 0.001) than vaccinated/naïve (VAC‐n; n = 472) and nonvaccinated/experienced (UNVAC‐ex; n = 63) subjects. Antibody levels correlated inversely with time elapsed since last vaccine dose in VAC‐n (Rho, −0.52; p < 0.001) but not in VAC‐ex (rho −0.02; p = 0.57). Heterologous booster shots resulted in increased anti‐RBD antibody levels compared with homologous schedules in VAC‐n, but not in VAC‐ex. NtAbs against Omicron BA.1 were detected in 94%, 75%, and 50% of VAC‐ex, VAC‐n and UNVAC‐ex groups, respectively. For Omicron BA.2, the figures were 97%, 84%, and 40%, respectively. SARS‐CoV‐2‐S‐reactive IFN‐γ T cells were detected in 73%, 75%, and 64% of VAC‐ex, VAC‐n and UNVAC‐ex, respectively. Median frequencies for both T‐cell subsets were comparable across groups. In summary, by April 2022, around half of the VC population had been infected with SARS‐CoV‐2 and, due to extensive vaccination, displayed hybrid immunity.